Pengukuran Kinerja Bidan dalam Pelaksanaan Antenatal Care Terintegrasi Di Wilayah Kerja Puskesmas Cipeuyeum Kabupaten Cianjur: Performance Measurement of Midwives in the Implementation of Integrated ANC in the Work Area of the Cipeuyeum Health Center, Cianjur Regency - Suryani, Yayan (Dohara POAJ, 2021)
Introduction: Antenatal care is a service for individuals who are preventive care to prevent problems that are not good for both mother and fetus to go through labor healthily and safely. The purpose of this study was to determine the relationship between supervision, work motivation, and resources and the performance of midwives in Integrated ANC services at Cipeuyeum Health Center in 2019. Methods: This study used descriptive analytic methods using a cross-sectional approach. The statistical test uses the chi-square test. The population in the study amounted to 32 and the sample amounted to 32 respondents. The sampling technique uses total sampling. Results: The results showed that midwife performance in ANC services was good (56%), supervision was good (63%), resources were good (59%) and work motivation was good (53%). There is a significant relationship between supervision (P-value 0.017), resources (P-value 0.003), and work motivation (P-value 0.004) on the performance of midwives in ANC services at Cipeuyeum Health Center in Cianjur in 2019. Discussion: The performance of midwives in integrated ANC services is good, supervision is good, resources are good, and work motivation is good. So that there is a significant relationship between supervision, resources, work motivation on the performance of midwives in integrated ANC services at the Cipeuyeum Health Center, Cianjur Regency.